The Effect of Word Clap Game in Improving Students’ Vocabulary Achievement at the Eighth Grade of SMPN 19 Kendari - Nur Iman Sai; Tambunan Tambunan; Amiruddin Rahim (Halu Oleo University, 2019)
Word clap game is a game that uses claps and collaboration with other students. The aim of this study was to find out whether there is or not a significant effect of Word Clap Game on the students’ vocabulary achievement at the eighth grade of SMP Negeri 19 Kendari. This study applied a quantitative study research method with SPSS 16 to analysis the data of students’ vocabulary achievement at the eighth grade of SMP Negeri 19 Kendari. Purposive Sampling was used to select the sample of the study. The samples were 16 students at grade VIII. 2 for experimental group and 17 students at grade VIII.1 for control group. The experimental group taught using Word clap game and the control group was taught by using conventional teaching technique. The data were analysed by using T-Test through SPSS program. The result of data analysis showed that students in experimental group performed better than the students in control group. It was proven by the result of the descriptive statistics that showed the mean score of the experimental group was 69, 37 while the mean score of the control group was 56, 47. Based on the findings, it was concluded that there was a significant effect of using word clap game on the students’ vocabulary achievement rather than using conventional teaching.Keywords:Word Clap Game; Vocabulary Achievement